Profitability of Flower Production and Marketing System of Bangladesh (Bangladesh Journal of Agricultural Research, 2012)
This study examines the production and profitability of some selected flowers in comparison with their competing crops. The study also attempts to identify the value chains and channels of flower marketing in Bangladesh. Stratified random sampling method was used to collect Primary data collected from the 32 farmers of Guptergaon under Phulpur Upazila in Mymensingh district and from the 21 flower traders, retailers and wholesalers of different flower trading zones in Dhaka city. The study reveals that gross margins of flower and vegetables per hectare were Tk.1,359,824.20 and Tk.46,362.14, respectively. The average marketing margin of three intermediaries i.e., BRAC, wholesaler-cum-retailer and retailer in Dhaka city, were Tk. 187.56, Tk. 638.39 and Tk.689.72 per 100 flowers, respectively. Lack of mother stock and their high price, price of fertilizer and insecticides, lack of scientific knowledge & training, attack by pest & disease, lack of extension work came out as major financial and technical problems of the flower farmers while inadequate & underdeveloped transportation & communication system, low market price, lack of market information, unstructured market are among major market related problems. On the other hand marketing intermediaries specified price instability, lack of adequate market information, lacking storage facilities, unsold flower, inadequate shop-space, demand fluctuation, strikes as their problems and constraints. Pertinent recommendations for facilitating flower production and developing an improved marketing system in Bangladesh include - a concentrated effort by the government and non-govt. agencies to provide  appropriate trainings to farmers and traders, to provide appropriate production assistance and storage facility & to build countrywide permanent trading infrastructure, deployment of an Market Information System (MIS) and deployment of Entrepreneur-friendly SME and credit policies and packages for ensuring a balanced growth of the floriculture industry. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11179 Bangladesh J. Agril. Res. 37(1): 77-95, March 2012